High-Precision Guide Stiffness Analysis Method for Micromechanism Based on the Boundary Element Method. (28th June 2021) - Yang, Manzhi; Lv, Zhenyang; Jing, Gang; Guo, Wei; Huang, Yumei; Li, Linyue; Wei, Kaiyang; Feng, Bin; Ge, Hongyu
Abstract : The guide stiffness performance directly affects the motion of the micromechanism in accuracy and security. Therefore, it is crucial to analyze the guide stiffness precisely. In this paper, a high-precision guide stiffness analysis method for the micromechanism by the boundary element method (BEM) is proposed. The validity and accuracy of the analysis method are tested by a guide stiffness experiment. In order to ensure the accuracy and safety during the micromechanism motion, a guiding unit of the micromechanism was designed based on the guiding principle. The guiding unit can provide parasitic motion and additional force in the motion of the micromechanism. Then, the stiffness equations of the beam element are derived by the boundary element method. The stiffness equation of straight circular flexure hinge is analyzed by rigid discretization and rigid combination, and the guide stiffness of the mechanism is investigated by rigid combination. Finally, according to the actual situation, the stiffness matrix of the guide rail ( Kb ) was proposed, and the analytical value of the guide stiffness was calculated to be 22.2 N/ μ m. The guide stiffness performance experiment was completed, and the experimental value is 22.3 N/ μ m. Therefore, the error between the analysis method and the experimental results is 0.45%. This study provides a new method for the stiffness analysis of high-precision micromechanisms and presents a reference for the design and stiffness analysis of complex structures. This method is helpful for stiffness analysis of the microrotary mechanism with high accuracy.